Innovative unified impact of magnetite iron nanoparticles and quercetin on broiler chickens: performance, antioxidant and immune defense and controlling of Clostridium perfringens infection - Al-Nasser, Afaf; El-Demerdash, Azza S.; Ibrahim, Doaa; Abd El-Hamid, Marwa I.; Al-Khalaifah, Hanan S.; El-borady, Ola M.; Shukry, Eman; El-Azzouny, Mona M.; Ibrahim, Mona S.; Badr, Shereen; Elshater, Nahla S.; Ismail, Tamer Ahmed; et al. (Frontiers in Veterinary Science, 2024)
Necrotic enteritis caused by Clostridium perfringens (C. perfringens) is characterized by poor performance and higher mortality rates in poultry farms. Novel dietary intervention involving bioactive molecules loaded into smart magnetized nano-system with a potent antioxidant function (quercetin-loaded Fe3O4-NPs), was evaluated for their impact on growth performance, intestinal immune and antioxidant defenses, and resistance against Clostridium perfringens in a necrotic enteritis challenge model. Four experimental groups comprising a total of 200 one-day-old Ross 308 broiler chickens were fed different diets: a control basal diet, a diet supplemented with quercetin (300 mg/kg), a diet with Fe3O4-NPs (60 mg/kg), and a diet with quercetin-loaded Fe3O4-NPs (300 mg/kg). These groups were then challenged with C. perfringens during the grower period. Dietary inclusion of quercetin-loaded Fe3O4-NPs prominently reduced C. perfringens colonization and its associated virulence genes expression, which subsequently restored the impaired growth performance and intestinal histopathological changes in challenged broilers. Quercetin-loaded Fe3O4-NPs supplemented group displayed higher Lactobacillus and Bifidobacterium counts, upregulation of intestinal host defense antimicrobial peptides related genes (avian β-defensin 6 and 12) and downregulation of intestinal inflammatory regulated genes (Interleukin-1 beta, C-X-C motif chemokine ligand 8, tumor necrosis factor-α, chemokine C–C motif ligand 20, inducible nitric oxide synthase and cycloox-ygenase-2). Intestinal redox balance was boosted via upregulation of catalase, superoxide dismutase, glutathione peroxidase and heme Oxygenase 1 genes along with simultaneous decrease in hydrogen peroxide, reactive oxygen species and malondialdehyde contents in groups fed quercetin-loaded Fe3O4-NPs. Overall, new nutritional intervention with quercetin-loaded Fe3O4-NPs impacted better immune and antioxidant defenses, attenuated C. perfringens induced necrotic enteritis and contributed to better performance in the challenged birds.